Application of Image Encryption Algorithm for Wireless Sensor Network in the Security Analysis of Public Big Data. (23rd April 2022) - Geng, Qiang; Yan, Huifeng
Abstract : To improve the security of the Wireless Sensor Network (WSN), the image encryption algorithm is studied. Firstly, the shortcomings of current image encryption algorithms are compared. Secondly, based on the chaotic system, the color image encryption algorithm of double chaotic cross-diffusion is built, and the encryption platform is constructed in combination with the current development of intelligent equipment. Finally, the performance of the constructed algorithm and platform is evaluated, and the correlation of adjacent pixel pairs in different color channels and different directions of image encryption is verified. The results indicate that in the designed image encryption platform, the channels of different color are encrypted in different directions, and the encryption effect is good. Compared with the evaluation platform, the practicability of the encryption algorithm is good. After the image is encrypted, the correlation between adjacent pixels is significantly reduced. The image is highly correlated with adjacent pixels in three directions in the first three channels of encryption. After the studied algorithm is encrypted, the correlation coefficient value of adjacent pixel pairs is greatly reduced, and the maximum reduction is 0.97. The information entropy of the red, green, and blue channels before encryption is lower than the information entropy of the three-color channels after encryption. The information entropy of the algorithm is closer to the optimal value of the information entropy. For the index values of Unified Average Changing Intensity (UACI) and Number of Pixels Change Rate (NPCR), the average UACI of the algorithm is 99.62%, while the average of the UACI of the literature algorithm is 98.33%. The NPCR value of the algorithm is 33.52%, while the NPCR value of the literature algorithm is 31.23%. The encryption and decryption time of the algorithm is shorter than that of the literature algorithm. The constructed algorithm has high efficiency of encryption and decryption. It provides a reference for the enhancement of the security of image data in the WSN.